2020
DOI: 10.1038/s41597-020-0424-8
|View full text |Cite
|
Sign up to set email alerts
|

First draft genome for the sand-hopper Trinorchestia longiramus

Abstract: Crustacean amphipods are important trophic links between primary producers and higher consumers. although most amphipods occur in or around aquatic environments, the family talitridae is the only family found in terrestrial and semi-terrestrial habitats. the sand-hopper Trinorchestia longiramus is a talitrid species often found in the sandy beaches of South Korea. In this study, we present the first draft genome assembly and annotation of this species. We generated ~380.3 Gb of sequencing data assembled in a 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…4J-4K and 4Q-4R). To our surprise, the best blast hits for obtained sequences were unknown proteins from other crustacean species (Table S4) Patra et al, 2020). It is important to note that different proteins of the pheromone/odorant-binding family bind a wide range of hydrophobic molecules and function beyond chemoreception (Pelosi et al, 2018).…”
Section: The Level Of Putative Carotenoid-binding Proteins Correlatesmentioning
confidence: 99%
“…4J-4K and 4Q-4R). To our surprise, the best blast hits for obtained sequences were unknown proteins from other crustacean species (Table S4) Patra et al, 2020). It is important to note that different proteins of the pheromone/odorant-binding family bind a wide range of hydrophobic molecules and function beyond chemoreception (Pelosi et al, 2018).…”
Section: The Level Of Putative Carotenoid-binding Proteins Correlatesmentioning
confidence: 99%
“…Currently, there are only two complete mitochondrial genome sequences of Platorchestia: P. parapacifica and P. japonica (Yang et al, 2017 ). Among 228 families consisting of more than 10,200 species in the order Amphipoda, only four genomes have been studied (Zeng et al, 2011 ; Rivarola-Duarte et al, 2014 ; Poynton et al, 2018 ; Patra et al, 2020 ), which includes the genome of talitrid Trinorchestia longiramus (Patra et al, 2020 ). Thus, we sequenced and assembled a reference genome for this Platorchestia species with an aim to set up a genetic platform for studying their taxonomical identification, divergence, and evolutionary history.…”
Section: Introductionmentioning
confidence: 99%
“…A phylogenetic analysis with 13 arthropod species suggested that P. hallaensis diverged from T . longiramus (Patra et al, 2020 ) during the Middle Cenozoic era. This talitrid genome will play a key role in further studies on the molecular mechanisms for adaptation of talitrids in diverse habitats and genomic variation across amphipods.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are only two complete mitochondrial genome sequences of Platorchestia: P. parapacifica and P. japonica (Yang et al, 2017). Among 228 families consisting of more than 10,200 species in the order Amphipoda, only four genomes have been studied (Zeng et al, 2011;Rivarola-Duarte et al, 2014;Poynton et al, 2018;Patra et al, 2020), which includes the genome of talitrid Trinorchestia longiramus (Patra et al, 2020). Thus, we sequenced and assembled a reference genome for this Platorchestia species with an aim to set up a genetic platform for studying their taxonomical identification, divergence, and evolutionary history.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative genomics among 13 arthropod species identified unique gene clusters in P. hallaensis, as well as contracted and expanded gene clusters in 13 arthropod species and their ancestors. A phylogenetic analysis with 13 arthropod species suggested that P. hallaensis diverged from T. longiramus (Patra et al, 2020) during the Middle Cenozoic era. This talitrid genome will play a key role in further studies on the molecular mechanisms for adaptation of talitrids in diverse habitats and genomic variation across amphipods.…”
Section: Introductionmentioning
confidence: 99%